2003
DOI: 10.1097/00126334-200306010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mitochondrial Toxicity in HIV-Uninfected Infants Born to HIV-Infected Mothers

Abstract: Although children born to HIV-infected (HIV+) women receiving antiretroviral therapy during pregnancy show virtually no adverse clinical effects at birth, the antiretroviral nucleoside analog drugs are known to damage nuclear and mitochondrial DNA. In this study, biomarkers of mitochondrial toxicity and genotoxicity have been examined in a well-characterized sample set consisting of infants born to HIV-uninfected (HIV-) mothers (n = 30), and HIV- infants (n = 20) born to HIV-infected (HIV+) mothers who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
1
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 40 publications
8
115
1
9
Order By: Relevance
“…2,3 Recent studies have found significantly higher mtDNA levels in peripheral blood mononuclear cells (PBMCs) of HIV-uninfected infants exposed to NA and to other ARV compared to ARV-unexposed infants at birth and in the first few weeks of life, [4][5][6] possibly to due compensatory mitochondrial activity in response to NA-induced stress. These findings contradict earlier studies, which reported decreased mtDNA in cord blood and PBMCs in ARVexposed infants at birth and at 1 and 2 years of age, [7][8][9] and a recent study that found mtDNA depletion with secondary respiratory chain compromise in placental tissue with ARV exposure. 10 Other findings include significantly lower mitochondrial RNA (mtRNA) levels at birth in NA-exposed vs. unexposed infants 4 and no difference in cytochrome c oxidase protein levels.…”
Section: Introductioncontrasting
confidence: 99%
“…2,3 Recent studies have found significantly higher mtDNA levels in peripheral blood mononuclear cells (PBMCs) of HIV-uninfected infants exposed to NA and to other ARV compared to ARV-unexposed infants at birth and in the first few weeks of life, [4][5][6] possibly to due compensatory mitochondrial activity in response to NA-induced stress. These findings contradict earlier studies, which reported decreased mtDNA in cord blood and PBMCs in ARVexposed infants at birth and at 1 and 2 years of age, [7][8][9] and a recent study that found mtDNA depletion with secondary respiratory chain compromise in placental tissue with ARV exposure. 10 Other findings include significantly lower mitochondrial RNA (mtRNA) levels at birth in NA-exposed vs. unexposed infants 4 and no difference in cytochrome c oxidase protein levels.…”
Section: Introductioncontrasting
confidence: 99%
“…4 However, AZT is not innocuous. [16][17][18][19] CDC currently recommends that children perinatally exposed to antiretrovirals should have long-term follow-up, including evaluation for late effects of these therapies, such as tumor onset, neurologic and neurodevelopmental deficits. 20,21 With an HIV seroprevalence among Hispanic mothers of 0.05% in our population, the number needed to screen would be more than 16,000 Hispanic gravidas to prevent a single case of perinatal transmission of HIV (based on a 25% baseline risk of vertical transmission and an optimal decrease to 8% with peripartum AZT).…”
Section: Discussionmentioning
confidence: 99%
“…In adipocytes from HAART treated patients, it has also been shown that NRTI administration correlated positively with mitochondrial DNA depletion [41,42] suggesting an etiology for the lipodystrophy imparted by HAART. There are also coherent experimental and clinical arguments for the existence of mitochondrial toxicity following perinatal exposure to AZT, alone or in combination with the NRTI 3TC [43,44]. Further it has been demonstrated that placental tissue of HIV-1-infected HAARTexposed pregnancies undergoes mitochondrial DNA depletion with secondary respiratory chain compromise [45] and also that HAART treated pregnant mothers can have children with mitochondrial dysfunction [46].…”
Section: Disruption Of Mitochondrial Function By Haartmentioning
confidence: 99%